Tide Guide (A graphical method of estimating height of tide at a given time or the time at which tide attains a required height in water areas subject to semidurnal tides) - Joshi, Madhav (The International Hydrographic Review, 2015)
This paper first describes and examines briefly various methods available to a navigator, port official or operator, etc., for determining height of tide at a given time and/or the time at which the tide will attain a given (required) height in water areas which are subject to semidiurnal tides. It then introduces a new graphical method for determining these two variables (height or time). Finally, it compares the results obtained by these methods and shows that the new method gives results within acceptable limits. Because of the complete absence of calculations and ease of use, this new method should be readily acceptable to users.